2016
DOI: 10.21608/jappmu.2016.48713
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Sodium, Potassium, Copper, Zinc and Heavy Metals in Camel Milk Reared Under Pasture and Farm Conditions in South Egypt

Abstract: The present study aimed to determine concentration of sodium, potassium, copper, zinc, lead and cadmium in camel's milk. The camels was divided into two groups, the first group reared under the traditional farms and the second reared under pasture system. The elements were determined by using atomic absorption (AA) flame spectrometry techniques. The results indicated that the overall mean of sodium and potassium contents in camel milk was 1848.54±571.2 and 3749.90±328.9 mg/l, respectively. While, the overall m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Higher concentrations of toxic heavy metals in spring milk may be due to the differences in feeding patterns of dairy animals in Iran, differences in the amount of soil ingested by animals and vegetation types in different seasons, differences in the amounts of rainfall in various seasons and finally using chemical Table 4. Standard allowed limit concentrations of Cd, Pb and Hg in milk samples [13][14][15][16][17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher concentrations of toxic heavy metals in spring milk may be due to the differences in feeding patterns of dairy animals in Iran, differences in the amount of soil ingested by animals and vegetation types in different seasons, differences in the amounts of rainfall in various seasons and finally using chemical Table 4. Standard allowed limit concentrations of Cd, Pb and Hg in milk samples [13][14][15][16][17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…[21] reported that the overall mean of Pb and Cd contents in camel milk in Egypt were 1056±105.85 and 8.00±0.21 ppb, respectively. The obtained results agreed with those reported by Saini et al(2007) [22], Meldebekova et al (2008)[23] and El-Bagermi et al (2014)[24].…”
mentioning
confidence: 99%
“…All analyzed milk samples obtained from animals grazing around industrial areas were contaminated by Cu and Al residues and have concentrations higher than that obtained from non-industrial areas. Previously, several studies were carried to detect the concentrations of Cu in camel milk in different areas in the world such as Qassim region of Saudi Arabia [ 34 ], Egypt [ 35 ], Lybia [ 36 ],Yobe State, Nigeria [ 37 ] and Kasuwan Shanu market in Maiduguri, Borno State [ 38 ], Kazakhstan [ 39 ], Kazakhstan [ 40 ], Nigeria [ 41 ], South Egypt [ 42 ], Iran [ 43 ] and China [ 12 ], they detected Cu at concentrations of 1.61, 1.90, 1.40, 1.34, 2.06 ±0.01, 0.065 ± 0.04, 0.07, 0.161, 0.065±0.02, 0.44 ± 0.03 and 0.248 ±0.55ppm respectively. While [ 12 ]detected Al in camel milk at concentration of 0.45± 0.2ppm.…”
Section: Discussionmentioning
confidence: 99%